Ampicillin Vs. Penicillin for In Utero Therapy - Douglas D. Glover; David Lalka; Gilles R. G. Monif (Hindawi Limited, 1996)
The pharmacokinetics of penicillin G and ampicillin are reviewed as they pertain to their potential use in in vitro therapy.